2020
DOI: 10.1021/acscatal.0c01537
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Antipoisoning Performance of Pd for Formic Acid Electrooxidation via an Ordered PdBi Intermetallic

Abstract: Pd-based materials are promising electrocatalysts for the formic acid oxidation reaction (FAOR) but suffer from poor durability due to the poisoning of adsorbed carbon monoxide species (COads). In this work, PdBi ordered intermetallic (O-PdBi) nanoparticles were prepared in an effort to mitigate the formation of adsorbed species like COads through isolating the Pd atoms. The enhanced antipoisoning capability of O-PdBi, relative to Pd, gave rise to superior activity and stability during FAOR. Differential elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 51 publications
3
68
0
Order By: Relevance
“…5b). [39,40] The shift in binding energies of Pd and Bi elements observed in meso-PdBi nanocages is ascribed to the unique Pd-Bi local bonding unit caused by the strong charge exchange between Pd-4d and Bi-(sp) orbitals. [41] To specifically distinguish the electronic structures, the Pd 3d XPS peaks were deconvolved to four peaks (Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…5b). [39,40] The shift in binding energies of Pd and Bi elements observed in meso-PdBi nanocages is ascribed to the unique Pd-Bi local bonding unit caused by the strong charge exchange between Pd-4d and Bi-(sp) orbitals. [41] To specifically distinguish the electronic structures, the Pd 3d XPS peaks were deconvolved to four peaks (Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…[ 196 , 197 ] Finally, the intermetallic Pd–Bi system covers a wide range of ordered phases; however, control over size and shape has been largely limited. [ 198 ] Recent efforts on this highly complicated system have offered supported nanoparticles of different intermetallic phases, such as Pd 3 Bi nanoparticles, by electrochemical dealloying of carbon‐supported β ‐PdBi 2 , [ 199 ] β ‐PdBi nanoparticles prepared via impregnation reduction at 600 °C, [ 200 ] and Pd 31 Bi 12 nanoparticles electrochemically deposited on carbon support at room temperature. [ 201 ]…”
Section: Synthetic Methods For Various Nmmnsmentioning
confidence: 99%
“…[30][31][32] Wang et al reported that PdBi alloys exhibited greatly enhanced activity and stability toward the formic acid oxidation reaction. 33 Integrating the nanoporous nanostructure with the alloying effect to form a nanoporous Pd-based alloy will pledge superior electrocatalytic applications. Despite obvious advances in nanoporous alloys, few examples have been reported for ternary nanoporous PdCuAg alloys partially due to the failure of so-templates in navigating the growth of metals with different growth kinetics and crystallinities.…”
Section: Introductionmentioning
confidence: 99%